A silent look at the teaching and learning of belly dance and the stereotype applied to practitioners: An experience report - Conceição, Valkíria Niina Mariano da; Gadelha, Jhonatan Gomes (Seven Editora, 2024)
This study investigated the benefits of practicing belly dance and explored the phenomenon of prejudice within the teaching of this modality. Using a qualitative review approach, the historical context of belly dance, its relationship with physical education and the teaching/learning process were analyzed. The results showed that belly dance contributes to integral education, promoting the appreciation of life and improving the health and quality of life of practitioners. It was concluded that the body language of dance can be a powerful tool for expressing feelings and emotions, as well as providing a connection with cultural roots and promoting female self-esteem. Thus, prejudice towards belly dancing is unjustified, as it offers an enriching and empowering form of expression. DOI:https://doi.org/10.56238/sevened2024.007-085